A Bayesian Reconstruction of a Historical Population in Finland, 1647–1850. - Voutilainen, Miikka; Helske, Jouni; Högmander, Harri (Demography (Springer Nature), 2020)
This article provides a novel method for estimating historical population development. We review the previous literature on historical population time-series estimates and propose a general outline to address the well-known methodological problems. We use a Bayesian hierarchical time-series model that allows us to integrate the parish-level data set and prior population information in a coherent manner. The procedure provides us with model-based posterior intervals for the final population estimates. We demonstrate its applicability by estimating the long-term development of Finland's population from 1647 onward and simultaneously place the country among the very few to have an annual population series of such length available.